Application under peptide bioregulators surgical treatment of chronic periapical odontogenic infection in elderly and senile - A. G. Slugina; D. V. Balin; A. A. Serikov; A. K. Iordanishvili (Кубанский научный медицинский вестник, 2015)
This article analyzes the clinical trial on the use of peptide bioregulators «kartalaks», produced by the St. Petersburg Institute of bioregulation and gerontology, on the course of reparative osteogenesis jaw after surgical treatment of chronic periapical odontogenic foci of infection in older age groups. With the help of clinical and radiological methods of research by the authors proved the effectiveness of this drug on reparative osteogenesis in older age groups. The authors conclude that the use of biocontrol treatment is necessary for leveling age variations in the healing of posttraumatic defects jawbone and recommend the use of approved methods in gerontostomatologу.